Utilizing Compost Soil Conditioner in Beach Sand Soil as a Palm Oil (Elaeis guineensis Jacq) in Pre-nursery Media - Sri Suryanti; Ryan Firman Syah; Ichan Al Hafish (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The objective of this study was to assess the effect of the type and dose of compost on the growth of oil palm seedlings in pre nursery with coastal sandy soil. The other objective is to know the effect of the type of compost on the growth of oil palm seedlings in pre nursery with coastal sandy soil. Lastly, the study examines the right dose of compost that provides the best growth of oil palm seedlings in pre nursery with coastal sandy soil. The experimental design was set in a factorial completely randomized design (CRD) consisting of two factors from April to June 2020 at the Tridharma Research Station Faculty of Agriculture, INSTIPER. The first factor is the type of compost which consists of 2 levels, Lamtoro compost, and vermicompost. The second factor is the dose of compost consisting of 4 levels: control (without compost), 50 gr compost/polybag, 75 gr compost/polybag, and 100 gr compost/polybag. The research data were analyzed using analysis of variance (α =0,05), and if there was a significant effect, it was continued with the Duncan multiple range test ( α = 0,05). Parameters observed included seedling height, total leaf, leaf width, stem diameter, shoot dry weight, root dry weight, root length, and total roots. The results showed that no combination of types and doses of compost significantly affected the growth of oil palm seedlings in pre-nursery. Using vermicompost can significantly increase oil palm seedlings' leaf area and root dry weight. Using compost at a dose of 50 g/polybag increased seedling height, stem diameter, and root dry weight in pre-nursery of oil palm seedlings.